Nonsingular fast terminal control for the DFIG-based variable-speed hydro-unit. (1st April 2022) - Fu, Jianing; Yu, Xiangyang; Gao, Chunyang; Cui, Junda; Li, Youting
Abstract: Pumped storage power plants (PSPPs) with variable-speed hydro-units are credible when tackling the impact caused by the introduction of renewable energy into grids. However, the units suffer from instability when the grid transients occur because the adopted doubly-fed induction generators (DFIG) have a strong coupling and nonlinearity. Conventional controllers failed to handle this situation. Although the sliding mode controller (SMC) is robust enough, it has problems of infinite convergence time and chattering issues. Nonsingular fast terminal sliding mode controller (NFTSMC) - an advanced SMC - is a promising method to solve these problems. This paper took the DFIG-based variable-speed hydro-unit as the studied object and adopted a newly-designed NFTSMC in the rotor side converter to secure the stable operation of the unit. Especially, a feedback control law and a modified coefficient of the sliding mode surface were combined with the adaptive super-twisting algorithm to handle the additional information of the derivatives of the sliding mode surface and guarantee the theoretical stability. Simulations under load rejection, parameter variation, voltage dips were imposed on the unit. Results showed the proposed controller has lower settling times, oscillations, and less over-shooting. The efficiency of the proposed controller is thus proved. Highlights: The modeling of the hydro-unit is enhanced by a detailed hydro-turbine model. Nonsingular terminal sliding mode and super-twisting algorithms reduce chattering. Modified coefficients prove the exponential stability based on Lyapunov theory. The robustness and ride-through performances are superior to those of PI control. NFTSMC shows an 83.3% decrease in oscillations at parameter variation.